Moksopaya - Textedition, Teil 6, Das Sechste Buch : Kritische Edition von Susanne Krause-Stinner und Anett Krause unter Mitwirkung von Peter Stephan. - Casmiriensis, Anonymus (Mokṣopāya / Historisch-kritische Gesamtausgabe, herausgegeben unter der Leitung von Walter Slaje., 2019)
In the 10th century, an anonymous author in Kashmir wrote a philosophical didactic poem on self-redemption: Mokṣopāya ("Way to liberation"). The Sanskrit version of this draft explanation of the world, unique in Indian intellectual history, handed down in Kashmir, is hereby published for the first time as a historical-critical text edition of its Six books with about 30,000 stanzas have been made accessible. Part 6 is the second of three sub-volumes of the sixth book "(About) Nirvāṇa". It contains 133 chapters of critically edited text and a summary of the content. In the didactically structured work, Prince Rāma goes through a gradual process of knowledge, through which the sage Vasiṣṭha guides him with the help of philosophical instructions and vivid literary narratives. In this volume, chapters 119-158, which have never been published in full before, deal with the so-called yoga stages and their states of consciousness. The reality supposedly experienced in the waking state is identified as merely a temporally extended dream. The story of the god Indra, who hid himself in a speck of dust that he never left because he created entire universes in it, illustrates the purely spiritual nature of all creation beyond the laws of matter. Among the seven parables, the "Narrative of the Stone" also stands out, portrayed by Vasiṣṭha more in the role of a living eyewitness than of an enraptured sage. While initially the omnipresence and simultaneity of all creations is depicted visually, a socio-culturally revealing one develops, but not easy to interpret drama with apocalyptic scenes.